The making of the Magdalen : preaching and popular devotion in the later Middle Ages - Jansen, Katherine Ludwig, 1957- (Princeton University Press, 2000)
"Best known during the Middle Ages as the prostitute who became a faithful follower of Christ, Mary Magdalen was the most beloved female saint after the Virgin Mary. Why the Magdalen became so popular, what meanings she conveyed, and how her story evolved over the centuries are the focus of this compelling exploration of late medieval religious culture." "Through the lens of medieval preaching, as well as the responses of those who heard the sermons preached, Katherine Jansen brings to light previously unpublished sermons to show how and why the mendicant friars transformed Mary Magdalen, a shadowy gospel figure, into an emblem of action and contemplation, a symbol of vanity and lust, a model of perfect penance, and the embodiment of hope and salvation. Jansen also draws on a variety of historical sources - from saints' lives to patronage patterns - to examine the laity's reception of the saint. She reveals that the laity's devotion to Mary Magdalen departed in significant ways from the friars' image of the saint, signaling a major development in popular religious practice and personal piety." "The making of the Magdalen will appeal to readers of medieval history and religion, to those with an interest in the study of women, sexuality, and gender, and to those who are interested in saints throughout the ages."--Jacket